Root System Architecture and Physiological Characteristics of Soybean (Glycine max L.) Seedlings in Response to PEG6000-Simulated Drought Stress - Vincent Ishola Esan; Idowu Arinola Obisesan; Timothy Oyebamiji Ogunbode (International Journal of Agronomy)
The production of soybean is restricted in sub-Saharan Africa by several stress conditions, including drought because its production is exclusively rain-fed. Identifying drought resistant varieties is of paramount importance. Thus, the objectives of this work were to (i) evaluate the effect of polyethylene glycol 6000 (PEG6000) on soybean at the seedling stage, (ii) determine the root system architecture and physiological characters to water deficit stress, and (iii) establish the correlation among the quantitative variables responsible for drought tolerance in soybean varieties. Twenty soybean accessions (G1 to G20) were subjected to 10% PEG6000 concentration at seedling stages under a controlled environment using a randomized complete block design with 3 replicates. Vegetative growth data were collected. Highly significant differences P<0.0001 of proline, carotenoid, chlorophyll a, and chlorophyll b contents were recorded among the 20 accessions in response to PEG application. G16 and G19 had the highest carotenoid, highest chlorophyll a, and chlorophyll b. The highest dry weight was observed in G16 and G10, while the number of leaves was recorded in G19 and G17. G4, G9, G10, and G13 demonstrated the highest dry weight. The PEG-simulated drought stress reduced the average root diameters and the number of lateral roots of all 20 accession plants. G1, G3, G4, G8, G9, and G15 had the longest roots than the control plants as a mechanism to withstand drought stress by seeking water in the deep. Number of leaves was significantly and positively correlated with shoot dry weight, root dry weight, and root diameter but was significantly and negatively correlated with canopy wilting. Proline content was significantly and positively correlated with carotenoid, chlorophyll content, chlorophyll a, and chlorophyll b. G10, G19, G9, G6, G16, G17, G20, G16, and G18 are the tolerant cultivars to drought stress on the basis of growth, physiological, and root system architecture.